Microstructural Analysis of Austempered Ductile Iron Castings - Baris Cetin; Kemal Davut; Ebru Arslan; Mustafa Can Uzun; Halim Meco (Hittite Journal of Science and Engineering, 2016)
A ustempered ductile iron ADI castings have a wide range of application areas in engineering designs due to their promising mechanical properties and lower cost. ADI has very good strength and toughness values at the same time its ductility is relatively high compared to most of the other cast irons. These promising mechanical properties originate from combination of specific graphite and matrix microstructure. The size, shape and fraction of graphite as well as the matrix microstructure influences the mechanical properties. In this paper the efforts regarding to a localization project of ADI is presented. In a more detailed manner, the first locally produced ADI which cannot satisfy the mechanical properties stated in ISO 17804 is compared with the original sample which is conform with the standard. The two pieces are inspected by mechanically and microstructurally by means of which necessary actions are detected for the local production. In other words the relation between the macro mechanical properties and the microstructural conditions are tried to be clarified